Kajian Semiotik pada Tradisi Tingkeban (tujuh bulanan) Etnis Jawa di Desa Persatuan Kabupaten Asahan - Ariska Erawati; Rosmawaty Harahap; Elly Prihasti Wuriyani (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
Tingkeban is a culture that has been passed down from generation to generation and has become a habit, this tradition is passed down orally. Each ethnic group has its own traditions, including the Javanese, as the researcher discussed, namely the tingkeban tradition, this tradition is one of the Javanese ethnicities which discusses the seven-monthly thanksgiving process during pregnancy. The research method used is by interviewing a resident who usually leads the tingkeban tradition in the Unity Village of Asahan Regency. In this oral tradition, semiotic aspects or signs are found in every verbal and nonverbal aspect.